Long-run Consequences of Exposure to Natural Disasters - Krzysztof Karbownik; Anthony Wray (Center for Economic Studies and ifo Institute (CESifo), 2016)
We utilize the individual-level World War I Draft Registration Cards matched to late-nineteenth century hurricane paths and the 1940 U.S. Census to explore whether fetal and early childhood exposure to stress caused by hurricanes affects human capital development and labor market outcomes in adulthood. Difference-in-differences estimates indicate that white males who were born in the South and experienced a hurricane either in utero or as infants had lower income at ages 42 to 53. They are robust to alternate specifications of either the treatment or outcome variables, as well as changes in the tolerance for imperfectly matched historical data.
Keywords: I10; J24; Q54; 330; prenatal stress; natural disasters; labor market outcomes